Preventive Analysis of Polymer Leakage in Injection Molding Machines and Its Impact on Production Efficiency - Muhamad Rafli; Dandi Maulana; Tri Rachmadi; Takuya Takuya; Yudi Prastyo (Lentera Ilmu Nusantara, 2025)
This study examines the causes and impacts of polymer leakage in a 500-ton injection molding machine, which frequently occurs at the nozzle and sprue bushing junction. Leakage is caused by seal wear, excessive injection pressure, and nozzle misalignment, which enlarges microgaps. Measurements show that at a pressure of 150 MPa and a temperature of 250°C, the leakage rate reaches 20–100 ml/h. Through Autodesk Moldflow simulations, the nozzle-sprue transition area was identified as the point of maximum pressure (152 MPa) with the highest leakage potential, thereby extending conventional maintenance diagnostics through simulation-based identification of critical stress zones rather than relying solely on routine visual inspection. After optimizing the design and process parameters including reducing the injection pressure to 140 MPa, using heat-resistant Viton seals up to 250°C, and readjusting the nozzle position the leakage rate decreased by 70% (from 60 ml/h to 18 ml/h). The output of this study is a leak prevention model based on visual inspection, direct measurement, and numerical simulation, which distinguishes this work from standard industrial troubleshooting by integrating predictive simulation with quantitative cost-saving analysis, enabling an increase in production efficiency by ± 5 percent and operational cost savings of approximately US1,800 per year per machine.